Case report: The origin of transmantle-like features - Matsuo, Takeshi; Fujimoto, So; Komori, Takashi; Nakata, Yasuhiro (Frontiers in Radiology, 2022)
The transmantle sign is considered to be a magnetic resonance imaging feature specific to patients with type II focal cortical dysplasia; however, this sign can be difficult to distinguish from other pathologies, such as a radial-oriented white matter band in tuberous sclerosis. Here, we report a case showing a high-intensity area on T2-weighted and fluid-attenuated inversion recovery images extending from the ventricle to the cortex associated with atypical histopathological findings containing corpora amylacea. This case demonstrates that some instances of transmantle signs may be due to corpora amylacea accumulation.